Analisis Gaya Bahasa Sindiran Dalam Acara Lapor Pak di Kanal Youtube - Rahayu, Sri; A, Al-Afandi; R, Rosma; Yulyn, Mysyon; Afik, Moh. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe: (1) Types of satirical language in the Lapor Pak program on the Youtube Channel, (2) The meaning of the satirical language style of the Lapor Pak program on the Youtube Channel. This type of research is a qualitative descriptive method. The data source for this study is the Lapor Pak Youtube Channel. The research data is in the form of quotes that can be formulated as a satirical language style based on the speech on the Lapor Pak Program on the Youtube Channel. The data collection techniques in this study are listening techniques and note-taking techniques. The data analysis technique is carried out by: (1) Transcribing the utterances spoken by the Lapor Pak actors which contain satirical language styles (2) classified in the form of a table based on the forms and meanings of the language styles, (3) explaining the meaning of the satirical language style expressed (4), Explaining the forms and meanings of the satirical language style spoken by the actors in the Lapor Pak content on the YouTube channel based on the results of data classification in the table. and (5) Summarizing the findings that have been analyzed. Based on data analysis and discussion, the results of the study showed that speakers used 20 data of satire. The satire styles found were irony, cynicism, sarcasm, satire and innuendo. The dominant satire style on the Lapor Pak Event on the Youtube Channel is ironic satire.